Active targeting in a random porous medium by chemical swarm robots with secondary chemical signaling - Grančič, Peter; Štěpánek, František (Physical review. E, Statistical, nonlinear, and soft matter physics, 2011)
The multibody dynamics of a system of chemical swarm robots in a porous environment is investigated. The chemical swarm robots are modeled as brownian particles capable of delivering an encapsulated chemical payload toward a given target location and releasing it in response to an external stimulus. The presence of chemical signals (chemo-attractant) in the system plays a crucial role in coordinating the collective movement of the particles via chemotaxis. For a number of applications, such as distributed chemical processing and targeted drug delivery, the understanding of factors that govern the collective behavior of the particles, especially their ability to localize a given target, is of immense importance. A hybrid modeling methodology based on the combination of the brownian dynamics method and diffusion problem coupled through the chemotaxis phenomena is used to analyze the impact of a varying signaling threshold and the strength of chemotaxis on the ability of the chemical robots to fulfill their target localization mission. The results demonstrate that the selected performance criteria (the localization half time and the success rate) can be improved when an appropriate signaling process is chosen. Furthermore, for an optimum target localization strategy, the topological complexity of the porous environment needs to be reflected.
Keywords: Chemotaxis; poréznost; stochastické procesy; biologické modely; Porosity; Stochastic Processes; Models, Biological; chemotaxe; chemotaktické faktory; Chemotactic Factors